Holocene environmental changes recorded by magnetic parameters of sediments in the Yangtze River Delta and implications for prehistoric cultural development - Guiye Zhang; Longsheng Wang; Shouyun Hu; Mingming Ma; Jiawen Zhao; Yanjun Ge; Lin Zeng; Xianbin Liu (Estuarine, Coastal and Shelf Science, 2026)

Critical overview of Peracetic acid-based advanced oxidation processes: Evolution, fundamentals and water treatment applications - Yongbo Yu; Jiaxin Yu; Haochen Zhang; Yongchao Mu; Yanjun Xin; Bin Zhang; Jun Ma (Chemical Engineering Journal, 2026)

Axial bearing capacity of composite post-grouted piles in clay: A model test investigation - Qinke Wang; Shuai Cao; Yanjun Guo; Jianlin Ma; Xiuli Du (Transportation Geotechnics, 2026)

Optimization of zeotropic series cycle for improved temperature matching and energy efficiency in compact household refrigerators - Bingqi Li; Yanjun Du; Xudong Ma; Yuting Wu; Che Wang; Jie Lin; Haiqing Guan; Lubing Wang (International Journal of Refrigeration, 2026)

Progressive Failure Mechanism and Prediction Model of Geogrid‑Reinforced Embankments under Long‑Term Service Conditions in Xinjiang, China - Weijia Sun; Caijin Wang; Xuejun Liu; Liangfu Xie; Yanjun Li; Yan Wang; Yuelong Ha; Chuanhong Qiang; Weilin Ma; Annan Zhou; Songyu Liu (Transportation Geotechnics, 2026)

Molecular mechanisms and environmental implications of thallium complexation with butyl xanthate - Ling Ma; Yanjun Wang; Yao Jin; Mengqiang Fan; Mengke Li; Yuehui Chen; Cao Liu; Yun Liu; Zhimin You (Journal of Hazardous Materials, 2026)

Experimental Study on the Extreme Wave Run-Up Phenomenon of a Semi-Braceless Floating Wind Turbine Foundation Under Focusing Waves - Yanjun Mao; Yu-Fei Wu; Xiaoxu Huang; Xiaozhou Ma; Guohai Dong (Oceans, 2026)
A series of physical model tests of a semi-braceless floating wind turbine foundation (FOWT) under freak waves was conducted in the present work. The extreme wave run-up phenomenon on the FOWT columns was reported and investigated. The back column exhibits a median wave run-up amplification factor of 1.65 (a 65% rise from the baseline condition), with the maximum recorded value hitting 3.18, marking a 218% amplification compared to the reference wave run-up. Four factors contribute to this phenomenon, including the wave-trapped mode between columns, the shoaling effect of the pontoons, the relative motion between the platform and the wave surface, and nonlinear wave run-up. The extreme wave run-up corresponds to violent wave dynamic pressures, showing nonlinear column pressure distributions. Steeper local freak waves can lead to higher wave dynamic pressures on the columns, and slamming pressures occur under breaking waves in some harsh wave conditions. The peak slamming pressure on the back column reaches 300% of that on other columns. The wave run-up and wave pressures on the columns are relevant to the structure’s load level, which is crucial to the safety of the engineering design.

Surface water-groundwater interaction and its hydrogeochemical implications at northern foothills of the Qinling Mountains, China: New insights from the Heihe River Basin - Yuan Liu; Panpan Xu; Hui Qian; Jianbing Peng; Yanjun Shen; Jun Ma; Qiming Wang (Journal of Hydrology, 2026)

Data-driven insights into real-world N2O emissions across conventional and hybrid vehicles: Transient impacts and driving factor identification - Huayang Zhao; Mingshen Ma; Zhou Yin; Han Jiang; Haiguang Zhao; Lei Zu; Yitu Lai; Yunjing Wang; Yanjun Wang; Hang Yin; Yan Ding (Journal of Hazardous Materials, 2026)

A synergistic metal ion–silane strategy enables fire-safe, water-repellent, and mold-resistant flattened bamboo board - Longchao Ma; Genmiao Wan; Yan Wang; Chenkai Dou; Danhe Liu; Yue Jiao; Hao Sun; Xinzhou Wang; Yi Chen; Qiliang Fu; Yanjun Li (Chemical Engineering Journal, 2026)

When defence mechanisms fail: Multi-omics evidence of antioxidant system collapse in Thymallus grubii liver under acute temperature stress - Xinchi Shang; Xinghua Che; Kai Ma; Huaifa Chen; Lanlan Zhang; Huizhi Sun; Yanjun Li; Meiqi Xing; Wei Xu; Wenhua Wu; Yongquan Zhang (Marine Pollution Bulletin, 2026)

Intensifying ocean stratification reduces vertical phosphate supply and carbon sink magnitude - Rui Wang; Xuegang Li; Jinming Song; Zhibo Wang; Shanshan Liu; Guorong Zhong; Yanjun Wang; Jun Ma; Huamao Yuan; Liqin Duan (Limnology and Oceanography, 2026)
In recent decades, global warming‐driven ocean stratification has profoundly affected nutrient cycling. As the largest marginal sea in the northwestern Pacific, the South China Sea (SCS) provides a representative setting to examine these responses. Based on two decades of temperature, salinity, and nutrient datasets, we quantified the evolution of stratification in the SCS, its impacts on the upward transport of deep‐water phosphate (PO 4 3− ), and the resulting changes in carbon sink. Results show an increasing intensification of stratification, with an upward shift of the thermocline's upper boundary, a downward shift of its lower boundary, increased thickness, and weakened vertical mixing. Despite enhanced external inputs from rivers and atmospheric deposition and reduced phytoplankton consumption of PO 4 3− in the mixed layer, PO 4 3− concentrations have declined persistently, indicating a substantial reduction in nutrient flux from the deep water across the thermocline into the surface layer. The minimum net reduction of PO 4 3− in the upper water column (mixed layer plus thermocline) was −0.047 Gmol·yr −1 . This decline in PO 4 3− supply constrained primary production and reduced CO 2 uptake, leading to an estimated carbon sink reduction of 2.21 × 10 5 t CO 2 ·yr −1 in the SCS.

Sophaline B inhibits non-small cell lung cancer by activating NLRP3/caspase-1/GSDMD-dependent pyroptosis and PI3K/AKT/mTOR-mediated autophagy - Yibo Hou; Zhongfu Wang; Yang Wu; Ting Deng; Siyu Yang; Shaohua Ma; Yubo Zhang; Ding Luo; Yanjun Chen; Xiaoyong Dai (Natural Product Research, 2026)

Effect of environmental factors and the photodegradation of methylene hygromycin in actual water samples by Pr3+-doped bismuth tungstate - Min Zhou; Lanfang Ma; Yanyan Wang; Yanjun Fang; Rongying Yang; Fujun Liu (Journal of Water Process Engineering, 2026)

SIRT1 protects against UVA-induced photoaging by suppressing oxidative stress and FOXO3a acetylation in human dermal fibroblasts - Wenjuan Ma; Min Jiang; Jingtao Zhang; Wenjie Liu; Yanjun Dan; Wenjia Sun; Li Ma; Leihong Xiang; Jie Ren (Journal of Photochemistry and Photobiology B: Biology, 2026)

Temperature sensitivity and rainfall heat flux drive rapid mass loss of low-latitude glaciers in the Southeastern Qinghai–Tibet Plateau - Yanjun Che; Shijin Wang; Yun Cao; Weiwei Lv; Xinggang Ma; Congzheng Han; Jian Zhong; Rong Wu (CATENA, 2026)

SEC10 suppresses KLF15-mediated transcriptional activation of JAK1 and promotes BoHV-1 replication - Wenqing Ma; Xiao Yu; Yanan Xu; Fachao Sun; Mengrui Zhao; Xinlei Wang; Yanjun Huan; Xin Yin; Hongmei Wang; Hongbin He (Veterinary Microbiology, 2026)

Nanoplastics induce SH-SY5Y cell damage through oxidative stress and disruption of amino acid metabolism - Tianyi Ma; Yuyang Liu; Jingran Sun; Yanjun Fang; Yonghui Wang; Xiaoli Li; Nan Su; Mingzhu Liu; Zunquan Zhao; Jin Wu; Jialei Bai (Toxicology, 2026)

QTL mapping of maize ear traits and functional analysis of associated genes - Yanjun Dong; Jiawei Wu; Zongjie Wang; Yimeng Wang; Peng Jiao; Siyan Liu; Yiyong Ma; Shuyan Guan (Journal of Plant Physiology, 2026)

Accumulation pattern, source apportionment and risk assessment of soil heavy metals across diverse land use types: Insights from the northern foothills of Qinling mountains, China - Bingyao Huo; Yanjun Shen; Yibing Ning; Wei Shen; Penghui Ma; Zhijie Jia; Luqing Zhao; Junyan Zhao; Xing Chen; Tao Ding; Sirui Li; Jianbing Peng (CATENA, 2026)

Multi-Scale Fractal Dimension Analysis of Pore Structure and Its Controlling Factors in Marine–Continental Transitional Shale of the Late Carboniferous Benxi Formation, Ordos Basin, China - Yanjun Meng; Xinyu Zhang; Qin Zhang; Zhen Qiu; Wanli Gao; Haojie Ma (Natural Resources Research, 2026)

The Mesoscopic Mechanisms of Rock Mass Failure under Coupled Blasting and Unloading - Lixiang Xie; Yang Hu; Zhendong Leng; Jianhua Yang; Yanjun Qi; Chao Liu; Wenwei Ma (Rock Mechanics and Rock Engineering, 2026)

Experimental Study on Stratum Disturbance Response During Pipe Jacking Through Composite Strata Under Multi-factor Coupling Effects - Yanjun Ma; Xiaoping Cao; Honggang Wu; Huaxin Xu (Rock Mechanics and Rock Engineering, 2026)

Climate and vegetation-driven variations, ecological thresholds and mechanisms of ecosystem services in China’s drylands - Baolong Ma; Linlin Gao; Yanjun Xu; Xinyue Li; Yang Deng; Haijiang Yang (Environment, Development and Sustainability, 2026)

High-alumina fly ash-derived microwave absorbents with enhanced electromagnetic wave attenuation via alkaline activation and carbothermal reduction - Imrana Salisu; Xiaohui Wang; Shuhua Ma; Yanjun Ou; Helong Hui; Luoyun Xu (Waste Management, 2026)

Integrating very-high-resolution imagery, Sentinel-2 time-series data, and machine learning to map shrub fractional abundance across arid and semi-arid ecosystems in China - Zhonghua Liu; Yuhao Feng; Xin Cao; Josep Peñuelas; Adrià Descals; Daryl Yang; Ka Kin Cheung; Shuwen Liu; Ziyu Lin; Xiaoqiang Liu; Xiaoyong Wu; Han Ma; et al. (Remote Sensing of Environment, 2026)

Engineering Arabidopsis for improved yield and nutritional quality through heterologous expression of maize ZmERF118 gene - Zongjie Wang; Yang Zhao; Xinrui Ma; Yanjun Dong; Manyao Liu; Peng Jiao; Kaisheng Yu; Yimeng Wang; Yiyong Ma; Shuyan Guan (Plant Science, 2026)

Low-carbon mechanochemical stabilization of Hg-rich fly ash from hazardous waste incineration - Jiaxin Yin; Yubiao Ma; Yanjun Liu; Zhiyi Qu; Liefeng Wang; Jianxin Zhu; Yunfei Wang (Journal of Hazardous Materials, 2026)

Holocene climate optimum moisture variability in the monsoon marginal zone of northern China revealed by multi-proxy stalagmite records - Shouyi Huang; Yanjun Cai; Gang Xue; Xinhui Zhang; Mei He; Ruoxin Li; Yingying Wei; Le Ma; Xing Cheng; Haiwei Zhang; Hai Cheng (Global and Planetary Change, 2026)

Mechanisms linking straw return to soil phosphorus cycling in Chinese farmland: A meta-analysis - Tao Yushan; Wang Jie; Ma Xiaohan; Zhang Shuxiang; Guo Yanjun (Field Crops Research, 2026)

“Bundling regions” based optimization of planting structure for water conservation in the Yellow River Basin - Yilin Shen; Qingtao Ma; Ying Guo; Xiaolu Chen; Mengzhu Liu; Lu Deng; Yiding Zhu; Yanjun Shen (Journal of Geographical Sciences, 2026)

Enzyme immobilization on nanomaterials in food industry: current status and future perspectives - Lang Du; Yingzhuo Liang; Sifan Cui; Jianyang Wei; Jianqiao Liu; Shuling Zhang; Yuqing Zhang; Liya Zhou; Ying He; Li Ma; Jing Gao; Yanjun Jiang (Critical Reviews in Food Science and Nutrition, 2026)

Increasing carbon mitigation through enhanced oil recovery - YanJun Lu; QianBo Fan; JinXuan Han; ManPing Yang; JianGuo Ma; DaXin Zhou; HongJian Zhu; Yu Qi; HaoRan Ge (International Journal of Greenhouse Gas Control, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Intermittent blue light-dark cycles: A new strategy for enhancing triterpenoid production in medicinal Sanghuangporus vaninii - Yanjun Ma; Rong Li; Jiahui Li; Zilu Song; Fawen She; Xiaoyan Ma; Xuetai Zhu (Journal of Photochemistry and Photobiology B: Biology, 2026)

Se-doped MoS2/CoFe2O4/CNT heterostructures with enhanced electromagnetic wave absorption via structural optimization and phase engineering - Zhigang Wu; Jin Chen; Yuzhao Ma; Xiaofeng Yang; Yanjun Li (Chemical Engineering Journal, 2025)

Sorafenib induces intestinal toxicity by disturbing gut microbiota and activating the LPS/TLR4/NF-κB signaling pathway in mice - Yaning Xu; Yongshi Mo; Wenxin Zhou; Meirong Qin; Meifang Li; Guo Yin; Hansheng Yu; Yuchun Chen; Haiyan Du; Yibao Jin; Houshuang Huang; Chong Ma; et al. (Toxicology, 2025)

ZmThr1, a chloroplast-targeted regulator from maize, enhances growth and grain development but reprograms amino acid and starch metabolism in Arabidopsis - Zongjie Wang; Peng Jiao; Yanjun Dong; Xinrui Ma; Manyao Liu; Jianhua Zhang; Shuyan Guan; Yiyong Ma (Journal of Plant Physiology, 2025)

Controllable mesoporous wrinkling design realizes interfacial charge engineering in hierarchical MBene/MoS2 heterostructures for enhanced microwave absorption - Yiming Wang; Jin Chen; Bo Li; Meidan Que; Yuzhao Ma; Xiaofeng Yang; Yanjun Li (Chemical Engineering Journal, 2025)

Metabolite-derived spectral modelling can differentiate heat and drought stress under hot-dry environments - Wanlu Zhong; K.H. Cheng; Laiyin Zhou; Jiaoping Zhang; Fan Zhang; Guoyang Feng; Xinyu Zhang; Qin Ma; Yanjun Su; Shichao Jin; Hon-Ming Lam; Jin Wu (Remote Sensing of Environment, 2025)

Multidimensional characterization of microplastic pollution in subtropical urban soils: Combining geospatial analysis and polymer risk indexing - Aolei Du; Yanjun Li; Qiying Jian; Kai Zhang; Yutang Luo; Jun Yan; Peixin Du; Deborah M. Power; Ying Li; Yibing Ma (Journal of Hazardous Materials, 2025)

Sunlight-driven hydrogen peroxide activation via copper hydroxyphosphate with broad spectrum response for imidacloprid degradation: Mechanism insight and DFT calculation - Haoran Zhang; Jiang Li; Yujiao Liu; Sihao Fu; Tianjie Su; Lingyu Meng; Yunfei Wang; Nian Ma; Guocheng Liu; Qinghua Yan; Yanjun Xin; Shuaishuai Xin (Chemical Engineering Journal, 2025)

Comparative unravelling the antifungal activity and mechanism of oleuropein and matrine inhibiting the growth of phytopathogen Fusarium spp. - Jiaxin He; Jianmei Dong; Wenwen Zhang; Yaya Cheng; Jiali Xie; Xufeng Ji; Fazal Ullah; Yanjun Ma; Weibao Kong (Pesticide Biochemistry and Physiology, 2025)

Mechanistic insights into plasmon-mediated charge transfer in Pt@BiOBr/g-C3N4 S-scheme heterojunction for solar-driven water treatment - Jin Chen; Ke Li; Jie Yan; Suqing Qin; Yuzhao Ma; Xiaofeng Yang; Yanjun Li (Journal of Water Process Engineering, 2025)

Identifying nitrate pollution of groundwater based on aquifer vulnerability and surface nitrogen loads in the Northern Foot of the Qinling Mountains, China - Yixin Liu; Hui Qian; Yanyan Gao; Siqi Li; Xiaoxin Shi; Zhiming Cao; Qi Long; Yi He; Yandong Ma; Puxia Wu; Yanjun Shen (Journal of Hazardous Materials, 2025)

Identifying omitted high reactive VOCs emission sources in China based on new speciated emission inventory - Di Wang; Jinhong Du; Li Yang; Jinmin Zhao; Xinmin Zhang; Zhihao Zhang; Wenjuan Zhao; Weiqi Zhang; Yuzhe Zhang; Jinghua Ma; Wenjing Jin; Yanjun Ren; et al. (Journal of Cleaner Production, 2025)

Carbon footprint and environmental impact of reconstituted bamboo material based on life cycle assessment - Jingwen Chen; Yan Ma; Xiaomei Zhang; Nina Yan; Yanjun Li; Lei Xu; Zhichao Lou (Journal of Cleaner Production, 2025)

Magnetic characteristics of sediments in the northern Yangtze River delta since MIS3 and their responses to palaeoenvironmental changes - Guiye Zhang; Longsheng Wang; Xiaohui Wang; Shouyun Hu; Mingming Ma; Jiawen Zhao; Yanjun Ge; Lin Zeng; Xianbin Liu; Chao Zhan; Qing Wang (CATENA, 2025)

Shelter efficiency of windbreak influenced by stand configuration - Ruijie Zhang; Rui Ma; Yanjun Ma; Fu Zhang; Linyuan Wei; Gazangzhuoma Xie (Biosystems Engineering, 2025)

The impact of microplastics and nanoplastics on biological nitrogen removal processes: Exacerbating the greenhouse effect - Yuliang Zhu; Ben Ma; Dong Li; Tongshuai Liu; Yanjun Zhu; Huiping Zeng; Jie Zhang (Journal of Hazardous Materials, 2025)

Sustainable treatment of solid titanium-gypsum-waste using acidic titanium-white-wastewater to produce high-value α-hemihydrate gypsum - Yuru Wang; Mengqi Xiang; Jiangmei Yi; Ye Wang; Wenxiang Tang; Yanjun Zhong; Hua Meng; Xiaodong Ma; Zhiyuan Chen (Hydrometallurgy, 2025)

Reaction and transformation behaviors of ferric oxides and titanium oxide in diasporic bauxite during an alkaline hydrothermal process - Muhammad Ibrahim; Yanjun Ou; Shuhua Ma; Xiaohui Wang (Hydrometallurgy, 2025)

Annually laminated stalagmite inferred variations of precipitation and temperature in northern China over the last 150 years - Yingying Wei; Yanjun Cai; Xing Cheng; Gang Xue; Kang’en Zhou; Le Ma; Yanbin Lu; Shouyi Huang; Mei He; Hai Cheng; R. Lawrence Edwards (Climate Dynamics, 2025)

Geniposide Improves Corticosterone-induced Toxicity in PC12 Cells through the NMDARs and BDNF Pathway - Qi Ma; Yu Ma; Shizhuo Sun; Lei Yang; Tian Shi; Boxi Zhang; Bo Shang; Ruiyuan Zhou; Jingyuan Liu; Jiao He; Jing Hu; Yanjun Cao (Cell Biochemistry and Biophysics, 2025)

Signal-on aptasensors on paper-based platform: Application of multilayer MXene nanoquencher and stabilized luminescent carbon dots - Jincai Yang; Mingzhu Liu; Jin Wu; Tianyi Ma; Yanxuan Li; Yue Zhang; Jingran Sun; Xiaoli Li; Yanjun Fang; Yonghui Wang; Lingchao Cai; Yuan Peng; et al. (Journal of Hazardous Materials, 2025)

A new method for total organic carbon prediction of marine-continental transitional shale based on multivariate nonlinear regression - Xinyu Zhang; Yanjun Meng; Taotao Yan; Jinzhi Zhong; Zhen Qiu; Weibo Zhao; Liangliang Yin; Haojie Ma; Qin Zhang (Frontiers of Earth Science, 2025)

Piezo-promoted Fe3+/Fe2+ cycling in Bi4Ti3O12/α-FeOOH heterojunction for enhanced Fenton-like degradation of refractory organic pollutants: A sustainable strategy and mechanism insights - Wei Guo; Bingjie Yin; Chengjie Chen; Dingxun Ma; Shanshan Li; Guodong Zhang; Guangshan Zhang; Yanjun Xin; Qinghua Chen (Journal of Water Process Engineering, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Preparation of SCOF/UiO-66-NH2 immobilized laccase biocatalytic membrane for micropollutants removal from water - Tiantian Wang; Lingfeng Zhao; Guanhua Liu; Xiaoyang Yue; Xiaobing Zheng; Li Ma; Yunting Liu; Mimi Chen; Yanjun Jiang (Chemical Engineering Journal, 2025)

Optimizing geographical traceability models of Chinese Lycium barbarum: Investigating effects of region, cultivar, and harvest year on nutrients, bioactives, elements and stable isotope composition - Yanjun Ju; Hejiang Liu; Shuhui Niu; Lu Kang; Lei Ma; An Li; Yan Zhao; Yuwei Yuan; Duoyong Zhao (Food Chemistry, 2025)

Passivity-Based Sliding Mode Control for the Robust Trajectory Tracking of Unmanned Surface Vessels Under External Disturbances and Model Uncertainty - Luke Ma; Siyi Pang; Yao He; Yongxin Wu; Yanjun Li; Weijun Zhou (Journal of Marine Science and Engineering, 2025)
This study uses a port-Hamiltonian framework to address trajectory tracking control for unmanned surface vessels (USVs) under unknown disturbances. A passivity-based sliding mode controller is designed, integrating adaptive disturbance estimation and an RBFNN-based uncertainty estimator. Stability is rigorously proven, and simulations confirm superior tracking performance, strong disturbance rejection, and accurate uncertainty estimation.

Effects of fine particulate matter bound heavy metals on intentional self-harm deaths in Guangzhou, China, insight from core chemical constituents - Chunyan Gui; Han Zhang; Zhanlu Lv; Tao Liu; Shengbing Yu; Yanjun Xu; Hualiang Lin; Jianpeng Xiao; Wenjun Ma; Bin Luo; Ling-Chuan Guo (International Journal of Biometeorology, 2025)

The interactive effect of extreme weather events and PM2.5 on respiratory health among the elderly: a case-crossover study in a high-altitude city - Zhenxu Ning; Yanjun Ma; Shuzhen He; Genshan Li; Ting Xiao; Chunguang Ma; Jing Wu (International Journal of Biometeorology, 2025)

Actinobacteria derived from soybean/corn intercropping influence the subsequent wheat - Songhe Chen; Ruirui Li; Bo Lv; Yanjun Li; Junda Li; Mengzhen Zhang; Xiaoxiao Ma; Cunhu Wang; Ruineng Xu; Yonghong Wang; Hong Liao; Yongjia Zhong (Agriculture, Ecosystems & Environment, 2025)

A novel machine learning approach for reservoir temperature prediction - Haoxin Shi; Yanjun Zhang; Yuxiang Cheng; Jixiang Guo; Jianqiao Zheng; Xin Zhang; Yude Lei; Yongjie Ma; Lin Bai (Geothermics, 2025)

Hierarchical carbon-incorporated boron nitride derived from protein flocculation for efficient oxidative dehydrogenation of propane - Dong Li; Yanjun Chen; Mengyao Sun; Wenwen Ma; Zean Xie; Lian Kong; Shuchong Bai; Zhen Zhao (Chemical Engineering Journal, 2025)

High-risk nuclide screening and parameter sensitivity analysis based on numerical simulation and machine learning - Xin Zhang; Yanjun Zhang; Yu Zhang; Yuxiang Cheng; Qiangbin Liu; Hao Deng; Yongjie Ma; Lin Bai; Lei Liu (Journal of Hazardous Materials, 2024)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Balance of heat management and salt-resistance on solar interfacial evaporator actively adjusted by the electric field with periodically changed direction - Shijin Fu; Ziqi He; Yuzhao Ma; Xiuliang Liu; Deqiang He; Yanjun Chen (Desalination, 2024)

Impact of urbanized atmosphere-land processing to the near-ground distribution of air pollution over Central Liaoning Urban Agglomeration - Wenxi Zhang; Zhenxin Liu; Xiaolan Li; Yuhao Mao; Yanjun Ma; Hong Liao (Atmospheric Environment, 2024)

Sodium humate ameliorates LPS-induced liver injury in mice by inhibiting TLR4/NF-κB and activating NRF2/HO-1 signaling pathways - Weiming Ma; Kexin Liu; Yanjun He; Shouxiang Deng; Yun Liu; Dong Wang (Molecular Biology Reports, 2024)

Inhibition of Staphylococcus aureus biofilm by quercetin combined with antibiotics - Yanjun Ma; Xinyun Kang; Guiqin Wang; Shuangyan Luo; Xiaofeng Luo; Guilai Wang (Biofouling, 2024)

Visible-light-driven photobiocatalytic synthesis of chiral sulfoxides over immobilized chloroperoxidase on magnetic yolk–shell Fe3O4@Cu-H-TiO2 photocatalyst - Xiaoyang Yue; Yuying Hou; Cuiyao Cao; Xue Cao; Haolei Song; Yanjun Jiang; Liya Zhou; Ying He; Xiaobing Zheng; Li Ma; Shijie Li (Journal of Cleaner Production, 2024)

Precision detection method for ship shell plate molding based on neural radiance field - Xinhang Zhang; Daofang Chang; Yanjun Ma; Jiwang Du (Ocean Engineering, 2024)

Characterization of wax precipitation in wax-doped asphalt binders by variable-temperature polarized light microscope and improved viscosity algorithm - Hai Yuan; Junhao Liu; Bo Su; Jianmin Ma; Haibo Ding; Yanjun Qiu (Fuel, 2024)

Circulating metabolomics revealed novel associations between multiple ambient air pollutants exposure and chronic obstructive pulmonary disease incidence: Evidence from a prospective cohort study - Liangle Yang; Yanjun Guo; Yuxin Yao; Yujia Xie; Shiyu Yang; Bingxin Shang; Xiaojie You; Haoxiang Liu; Jixuan Ma (Environmental Pollution, 2024)

Variation of nitrate sources affected by precipitation with different intensities in groundwater in the piedmont plain area of alluvial-pluvial fan - Heping Sun; Wenbo Zheng; Shiqin Wang; Lin Ma; Leilei Min; Yanjun Shen (Journal of Environmental Management, 2024)

Highly efficient and secure recycling of neomycin fermentation residue by optimum temperature: Nutrients release, neomycin degradation and safety evaluation - Yuefei Li; Jiaqi Hou; Dong Wang; Junhao Ma; Weikai Sun; Mingxiao Li; Zhihao Sun; Yulin Liu; Guocheng Liu; Qinghua Yan; Qianwen Wang; Beidou Xi; et al. (Chemical Engineering Journal, 2024)

Effects of GPS flex power on DCBs, ionospheric delays and positioning - Yanjun Du; Yuanxi Yang; Xiaolin Jia; Yan Xiang; Wanqiang Yao; Ting Ma; Qin Li (Advances in Space Research, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

A comprehensive review of compression high-temperature heat pump steam system: Status and trend - Xudong Ma; Yanjun Du; Tian Zhao; Tingting Zhu; Biao Lei; Yuting Wu (International Journal of Refrigeration, 2024)

Unveiling the comprehensive performance and safety advancements in PVC films through environmentally friendly PMgLaCe-LDH incorporation - Yongchun Li; Lijuan Qiao; Yu Tang; Zhi Jia; Xiang Guan; Zhaocai Wang; Shuo Xu; Weilu Yang; Yunfei Ma; Yuting Qiao; Bingxin Liu; Li Gao; et al. (Chemical Engineering Journal, 2024)

Perspectives on the highly selective oxidation of copper-mediated C3N4-BiVO4 organic-inorganic hybrid catalysts and the efficient generation of reactive oxygen species - Qian Luo; Yue Chen; Yanjun Zhao; Shan He; Shirui Lv; Yuning Ma; Xintong Liu (Chemical Engineering Journal, 2024)

SPR effect and internal electric field in Pt@BiOBr/(001)-TiO2 S-scheme heterojunction for visible-light-driven photocatalytic degradation of tetracycline hydrochloride and dyes - Jie Yan; Jin Chen; Xiaofeng Yang; Yueying Wang; Xinle Wang; Jianye Shi; Jing Zhang; Yuzhao Ma; Yanjun Li (Journal of Water Process Engineering, 2024)

Associations of polychlorinated biphenyls exposure, lifestyle, and genetic susceptibility with dyslipidemias: Evidence from a general Chinese population - Yuxin Yao; Min Zhou; Qiyou Tan; Ruyi Liang; Yanjun Guo; Dongming Wang; Bin Wang; Yujia Xie; Haoyu Yin; Shiyu Yang; Bingxin Shang; Xiaojie You; et al. (Journal of Hazardous Materials, 2024)

Investigation on Uplift Behavior of Rock-Socketed Belled Piles in Horizontal and Inclined Ground Using 1-g Model Test and 3D Numerical Method - Qinke Wang; Zhongbo Hu; Yanjun Guo; Yukun Ji; Baolong Zhu; Jianlin Ma (Rock Mechanics and Rock Engineering, 2024)

Energy, exergy, economic, and environmental analysis of a high-temperature heat pump steam system - Xudong Ma; Yanjun Du; Biao Lei; Yuting Wu (International Journal of Refrigeration, 2024)

Facile dissolution of cellulose by superbase-derived ionic liquid using organic solvents as co-solvents at mild temperatures - Yuhui Ci; Yunqian Ma; Tianying Chen; Feiyun Li; Yanjun Tang (Carbohydrate Polymers, 2024)

A comparison of hydrothermal carbonization versus pyrolysis-activation for sludge-derived carbon materials on physiochemical properties and electrochemical performance - Qianqian Guo; Shixuan Qiao; Dongming Zhang; Zehuang Zhang; Fan Yu; Zhongqing Ma; Yanjun Hu (Biomass and Bioenergy, 2024)

Mammogram mass segmentation and classification based on cross-view VAE and spatial hidden factor disentanglement - Yingran Ma; Yanjun Peng (Physical and Engineering Sciences in Medicine, 2024)

An integrated study of constraining the initial 230Th of a stalagmite and its implications - Shouyi Huang; Yanjun Cai; Hai Cheng; Gang Xue; Xing Cheng; Mei He; Ruoxin Li; Le Ma; Yingying Wei; Yanbin Lu; Ling Yang; R. Lawrence Edwards (Quaternary Geochronology, 2024)

Communication Management and Data Compression Algorithm Design of BeiDou Transparent Transmission Terminal for Argo Buoy - Hongyu Li; Yanjun Fan; Yicheng Wen; Yanchao Zou; Qingfeng Ma; Shaobo Yang (Journal of Marine Science and Engineering, 2024)
The Argo buoy detects marine environmental data by making profile movements in the ocean and transmits the profile detection data to the shore base through the communication terminal. However, due to the large volume of data collected from profile detections and the continuous operation of the terminal, the remote communication of buoys is characterized by lengthy communication times and significant power consumption. A low-power Beidou transparent transmission terminal is designed to solve these problems in this paper. The terminal performs low-power operation management and power management for terminal remote communication. After the end of a communication process, the microcontroller turns the Beidou module power off and enters STOP mode. Before the next communication process begins, the serial port wakes up the microcontroller, which powers up the Beidou module. Before the remote communication, the microcontroller compacts the profile detection data collected by the buoy to reduce the quantity of remote communication data. In this paper, a variety of data compression methods are used to compare the compression rate, and the best compression method is selected according to the format characteristics of the data. The results show that the Beidou transparent transmission terminal of the Argo buoy can realize low power consumption for remote communication in ocean exploration. The terminal reduces power consumption by 77.282% per communication, and the average number of remote communications for each profile detection data are reduced by 55 times. The low-power Beidou transparent transmission terminal improves the battery life and is conducive to the long-term operation of the buoy.

Urban shrinkage in the regional multiscale context: Spatial divergence and interaction - Zuopeng Ma; Guolei Zhou; Jing Zhang; Yanjun Liu; Pingyu Zhang; Chenggu Li (Sustainable Cities and Society, 2024)

Catalytic stepwise pyrolysis for dechlorination and chemical recycling of PVC-containing mixed plastic wastes: Influence of temperature, heating rate, and catalyst - Yanjun Hu; Mingzhe Li; Nan Zhou; Hao Yuan; Qianqian Guo; Long Jiao; Zengyi Ma (Science of The Total Environment, 2024)

Biocatalytic membranes with crosslinked enzyme aggregates for micropollutant removal - Guanhua Liu; Luting Wang; Anan Zhao; Leijie Guo; Liya Zhou; Ying He; Li Ma; Yunting Liu; Jing Gao; Yanjun Jiang (Chemical Engineering Journal, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Mechanism of Antidepressant Action of (2R,6R)-6-Hydroxynorketamine (HNK) and Its Compounds: Insights from Proteomic Analysis - Chaohui Zhen; Chong Wang; Yanjun Ma; Yuli Pang; Feiyue Cai; Jiali Meng; Yuefei He; Ping Xiao; Jianxi Liu; Xi Mei; Shupeng Li; Guanzheng Wu; et al. (Molecular Neurobiology, 2024)

Monitoring the ecological restoration effect of land reclamation in open-pit coal mining areas: An exploration of a fusion method based on ZhuHai-1 and Landsat 8 data - Hongyu Wang; Wei Zhou; Yanjun Guan; Juan Wang; Rongrong Ma (Science of The Total Environment, 2023)

Experimental studies on the effects of thermal damage in coal-derived mudstones caused by high temperatures - Yanjun Shen; Ziyi Li; Cheng Peng; Bohan Yang; Tianchi Ma (Acta Geodaetica et Geophysica, 2023)

A dual-enzyme microreactor based on encapsulation and covalent bond for enzymatic electrocatalytic CO2 reduction - Guanhua Liu; Lirong Wang; Lihang Yan; Hao Zhao; Yaoxuan Li; Liya Zhou; Ying He; Li Ma; Yunting Liu; Jing Gao; Yanjun Jiang (Chemical Engineering Journal, 2023)

Degradation of dimethyl phthalate by morphology controlled β-MnO2 activated peroxymonosulfate: The overlooked roles of high-valent manganese species - Yanhao Wang; Yunlong Sun; Mengchun Gao; Yanjun Xin; Guangshan Zhang; Peng Xu; Dong Ma (Journal of Hazardous Materials, 2023)

High efficiency 2D/0D/3D Z-scheme rGO@g-C3N4/TiO2 nanobelt-tubes heterojunction for tetracycline degradation under visible light: Electrochemical synthesis, performance, and mechanisms - Xiaohan Ma; Guocheng Liu; Lu Wang; Shuaishuai Xin; Bin Zhang; Qinghua Chen; Qinghua Yan; Guangshan Zhang; Yingjie Zhang; Yanjun Xin (Journal of Environmental Chemical Engineering, 2023)

Micropore Structure Changes in Response to H2O2 Treatment of Coals with Different Ranks: Implications for Oxidant Stimulation Enhancing CBM Recovery - Yuan Zhao; Yanjun Meng; Kunjie Li; Sujuan Zhao; Haojie Ma (Natural Resources Research, 2023)

Mechanism study on a recyclable and clean process for boron removal from industrial-grade silicon using CrMnFeNiMe high-entropy alloy - Yong Liu; Zhihua Zeng; Yanjun Zhong; Wenxiang Tang; Ye Wang; Zhiyuan Chen; Wenhui Ma; Kazuki Morita (Journal of Cleaner Production, 2023)

Mechanism of adsorption capacity enhancement of coal due to interaction with high-pressure scCO2-water system - Siyuan Liu; Chuanjie Zhu; Yanjun Li; Sijia Hu; Xiangliang Zhang; Cong Ma (Gas Science and Engineering, 2023)

Study on detection method of microplastics in farmland soil based on hyperspectral imaging technology - Lijia Xu; Yanjun Chen; Ao Feng; Xiaoshi Shi; Yanqi Feng; Yuping Yang; Yuchao Wang; Zhijun Wu; Zhiyong Zou; Wei Ma; Yong He; Ning Yang; et al. (Environmental Research, 2023)

Combined contributions of cytochrome P450s (CYPs) and non-enzymatic metabolism in the in vitro biotransformation of anaprazole, a novel proton pump inhibitor - Fei Liu; Yanjun Xu; Li Wang; Xifeng Ma; Zhen Zhang; Xiaomei Zhuang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Enlarged fins of Tibetan catfish provide new evidence of adaptation to high plateau - Liandong Yang; Ning Sun; Honghui Zeng; Ying Wang; Wenjun Chen; Zufa Ding; Yang Liu; Jing Wang; Minghui Meng; Yanjun Shen; Jingliang Kang; Xiuhui Ma; et al. (Science China Life Sciences, 2023)

Structural characteristics and genetic mechanism of transfer zones in an extensional rift zone: An example from the Xihu Sag, East China Sea Basin - Yanjun Cheng; Zhiping Wu; Bin Xu; Jie Zhang; Yichen Chu; Yining Dai; Lili Xu; Wenjie Sun; Saiting Ma (Tectonophysics, 2023)

Activation of peroxymonosulfate with cobalt embedded in layered δ-MnO2 for degradation of dimethyl phthalate: Mechanisms, degradation pathway, and DFT calculation - Yanhao Wang; Yunlong Sun; Ruyun Wang; Mengchun Gao; Yanjun Xin; Guangshan Zhang; Peng Xu; Dong Ma (Journal of Hazardous Materials, 2023)

A smartphone-assisted ratiometric colorimetric and fluorescent probe for triple-mode determination of nitrite based on MnO2 nanoparticles and carbon quantum dots - Bo Peng; Chunjuan Wang; Xueyan He; Yongjun Ma; Min Zhou; Xin Ma; Shengguo Zhao; Yanjun Fang (Food Chemistry, 2023)

Seasonal evolution of aerosol loading and its vertical distribution in northeastern China from long-term satellite observations and model reanalysis - Hujia Zhao; Ke Gui; Yanjun Ma; Yangfeng Wang; Yaqiang Wang; Hong Wang; Yu Zheng; Lei Li; Lei Zhang; Huizheng Che; Xiaoye Zhang (Atmospheric Environment, 2023)

Efficiency and mechanism on photocatalytic degradation of fluoranthene in soil by Z-scheme g-C3N4/α-Fe2O3 photocatalyst under simulated sunlight - Guoliang Yang; Yan Jiang; Bingjie Yin; Guocheng Liu; Dong Ma; Guangshan Zhang; Guodong Zhang; Yanjun Xin; Qinghua Chen (Environmental Science and Pollution Research, 2023)

Identification and transcriptome data analysis of ARF family genes in five Orchidaceae species - Yiwei Bai; Yanjun Ma; Yanting Chang; Wenbo Zhang; Yayun Deng; Na Zhang; Xue Zhang; Keke Fan; Xiaomeng Hu; Shuhua Wang; Zehui Jiang; Tao Hu (Plant Molecular Biology, 2023)

Impact of clayey sediment compaction on pore water evolution and the release of iron - Yanjun Liu; Teng Ma; Juan Chen; Ziqi Peng; Cong Xiao; Wenkai Qiu; Rui Liu; Yao Du (Applied Geochemistry, 2023)

Associations of selenium exposure with blood lipids: Exploring mediating DNA methylation sites in general Chinese urban non-smokers - Xiuquan Nie; Ge Mu; Yanjun Guo; Shijie Yang; Xing Wang; Zi Ye; Qiyou Tan; Mengyi Wang; Min Zhou; Jixuan Ma; Weihong Chen (Science of The Total Environment, 2023)

Biodegradation of organic compounds in the coal gangue by Bacillus sp. into humic acid - Chenxu Liu; Shuhua Ma; Xiaohui Wang; Yanjun Ou; Hao Du (Biodegradation, 2023)

Orbital‐ to millennial‐scale variation of the speleothem δ 18 O record during Marine Isotope Stages 5 to 3 on the southeast Chinese Loess Plateau and its climatic and environmental implications - YANJUN CAI; HAI CHENG; XING CHENG; ZHENGGUO SHI; YANBIN LU; LE MA; CARLOS PÉREZ‐MEJÍAS; HAIWEI ZHANG; YINGYING WEI; GANG XUE; HANYING LI; MEI HE; et al. (Journal of Quaternary Science, 2023)
The Chinese Loess Plateau (CLP) is located in northern China, a region climatically dominated by the East Asian monsoon. Speleothem records from this region are crucial to fully understand the variability of the East Asian summer monsoon (EASM) and reconcile the disparity seen between loess records and speleothem δ 18 O records for the EASM. Here, we present an absolutely dated stalagmite isotope record spanning most of Marine Isotope Stage (MIS) 5 to MIS 3 from Xiaotian Cave, southeast CLP. The Xiaotian speleothem δ 18 O record is dominated by precessional variations and punctuated by notable millennial‐scale oscillations; in particular, the δ 18 O values in MIS 5e, 5c and 5a were in the same range, consistent with other speleothem δ 18 O records from the EASM region within quoted errors, verifying the difference between speleothem δ 18 O and loess records (e.g. magnetic susceptibility) and the proposition that those two archives may record different aspects of the EASM changes. The similar values in MIS 5e, 5c and 5a observed from the speleothem δ 18 O records in EASM regions, incompatible with the relatively higher North Hemisphere Summer Insolation (NHSI) during MIS 5e, were probably caused by an equivalent or even increased contribution of 18 O‐enriched moisture from the South China Sea and North Pacific, implying that an El Niño‐like state existed during MIS 5e. The Xiaotian δ 18 O values increased abruptly at ~121.7 thousand years (kyr) before the present ( bp , present refers to ad 1950), consistent with the trend seen in previously reported Chinese speleothem δ 18 O records, indicating an abrupt regime shift in atmospheric circulations or hydroclimate conditions in the Asian monsoon systems. It cannot be definitely ruled out that an increase in sea ice extent in the northern North Atlantic, responding to a decrease of NHSI, reached a threshold to have led to abrupt changes in the Asian summer monsoon (ASM) through rapid shifts in the position of circulation of the westerlies and/or in the position of Intertropical Convergence Zone (ITCZ). Here, we hypothesized that sea surface cooling in the tropical Indian and Pacific Ocean caused by the decreased summer insolation reached a threshold that eventually resulted in an abrupt shift to more positive precipitation δ 18 O, either through weakened convection over the tropical ocean, or through abrupt shifts in moisture transport and cycling of tropical moisture sources for the ASM. The Xiaotian speleothem δ 18 O record also shows centennial‐scale variability with amplitude up to 3‰ within MIS 5e. These changes are similar to variations recorded by the speleothem δ 18 O record from Tianmen Cave on the south‐central Tibetan Plateau and Shangxiaofeng Cave in Shandong Province, northern China, suggesting a heightened sensitivity of precipitation δ 18 O to climate changes at the marginal zone of the ASM even during the warm and humid MIS 5e interglacial. Climatic oscillations during MIS 5e appear to be comparable to those typical of the Holocene, implying rather unstable climate conditions during the Last Interglacial.

Analysis of Water Resonance in the Inner Domain of a Large Fixed Floating Tourist Platform Based on a 3D Non-Hydrostatic Model - Zhiqiang Liu; Yanjun Mao; Jun Ding; Chao Tian; Siyu Wang; Congfang Ai; Xiaozhou Ma; Guohai Dong (Journal of Marine Science and Engineering, 2023)
In order to meet the needs of marine tourism development, this paper analyzes the water resonance in the inner domain of a fixed floating tourist platform based on a 3D non-hydrostatic model. The tourist platform has a complex structure that is prone to the resonance of the water in the inner domain under wave actions. The water’s motion response in the platform’s inner domain under wave action is simulated numerically using numerical simulation methods. The non-hydrostatic model used in this paper is based on a semi-implicit method to solve the incompressible Navier–Stokes equations (NSE) and combines the immersed boundary method with the global continuity equations in the pressure zone (the flow zone under the structure) to approach the problem. In this paper, firstly, the resonant frequencies and resonant amplitudes of the water inside the box-shaped ship are calculated and compared with the experimental data to demonstrate the non-hydrostatic model’s accuracy in calculating the resonance problem of the water in the inner domain of a fixed floating platform. Secondly, the water’s resonant frequencies and resonant modes in the inner domain are calculated by numerical modeling of the floating tourist platform, including rare high-order resonance modes. We found that there are six resonance modes with complex shapes in the water of the inner domain of the tourist platform. Furthermore, the effects of the wall thickness, chord distance and draft of the annular tourist platform on the resonant amplitude values and modes of the water domain within the platform are analyzed in depth.

The Mesozoic tectonic evolution of the East China Sea Basin: New insights from 3D seismic reflection data - Yanjun Cheng; Zhiping Wu; Bin Xu; Yining Dai; Yichen Chu; Jie Zhang; Mingming Chen; Saiting Ma; Wenjie Sun; Lili Xu (Tectonophysics, 2023)

A case study on the migration of nuclides in the coupled vadose zone-groundwater system at a proposed spent fuel reprocessing site in Gansu, China - Xin Zhang; Yanjun Zhang; Yu Zhang; Xuefeng Gao; Yuxiang Cheng; Yongjie Ma; Peng Zhang; Xuhong Wang (Journal of Hydrology, 2023)

Using one-dimensional convolutional neural networks and data augmentation to predict thermal production in geothermal fields - Yunxing Yang; Yanjun Zhang; Yuxiang Cheng; Zhihong Lei; Xuefeng Gao; Yibin Huang; Yueqiang Ma (Journal of Cleaner Production, 2023)

Mapping China’s planted forests using high resolution imagery and massive amounts of crowdsourced samples - Kai Cheng; Yanjun Su; Hongcan Guan; Shengli Tao; Yu Ren; Tianyu Hu; Keping Ma; Yanhong Tang; Qinghua Guo (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Structural elucidation of a novel polysaccharide from Ophiopogonis Radix and its self-assembly mechanism in aqueous solution - Bei Wang; Bin Huang; Bing Yang; Liang Ye; Jingqi Zeng; Zhiwei Xiong; Yaping Chen; Shuchen Guo; Yanjun Yang; Weikun Ma; Maomao Zhu; Xiaobin Jia; et al. (Food Chemistry, 2023)

Construction of g-C3N4 with three coordinated nitrogen (N3C) vacancies for excellent photocatalytic activities of N2 fixation and H2O2 production - Yanjun Xue; Chaoqun Ma; Qingfeng Yang; Xinyu Wang; Shanna An; Xiaoli Zhang; Jian Tian (Chemical Engineering Journal, 2023)

Impact of thermal structure of planetary boundary layer on aerosol pollution over urban regions in Northeast China - Shuo Lu; Xiaolan Li; Tianliang Zhao; Yanjun Ma; Yangfeng Wang; Yunhai Zhang; Yuehan Luo; Yushan Xin (Atmospheric Pollution Research, 2023)

Impacts of snow cover on micrometeorological conditions and rural air quality in Northeast China - Xiaolan Li; Xiaofeng Guo; Yanjun Ma; Yangfeng Wang; Qingyu Jia; Rihong Wen; Yanbin Xie (Atmospheric Research, 2023)

What will the water quality of the Yangtze River be in the future? - Wenxun Dong; Yanjun Zhang; Liping Zhang; Wei Ma; Lan Luo (Science of The Total Environment, 2023)

Experimental research on the heat transfer characteristics of fluid flowing through rock with intersecting fractures - Yueqiang Ma; Quan Gan; Yanjun Zhang; Yibin Huang (Geothermics, 2023)

Mixed heavy metals exposure affects the renal function mediated by 8-OHG: A cross-sectional study in rural residents of China - Xiaoyu Tian; Xiaobing Shan; Li Ma; Chenyang Zhang; Mei Wang; Jie Zheng; Ruoyi Lei; Li He; Jun Yan; Xun Li; Yanjun Bai; Keqin Hu; et al. (Environmental Pollution, 2023)

Hollowing of nanoparticle membrane by sacrificing phase-inversion-formed nanohydrogel to enhance solar–steam generation efficiency - Yu Ma; Xiaoli Zhao; Yanjun Shen; Yi Wang; Bin He (Desalination, 2023)

The increasing big gap of carbon sink between the western and eastern Pacific in the last three decades - Guorong Zhong; Xuegang Li; Jinming Song; Baoxiao Qu; Fan Wang; Yanjun Wang; Bin Zhang; Detong Tian; Jun Ma; Huamao Yuan; Liqin Duan; Ning Li; et al. (Frontiers in Marine Science, 2022)
The Pacific Ocean is one of the important carbon sink regions, and there is a significant west-east difference in sea-air CO 2 flux. However, the influence of the long-standing greater CO 2 uptakes in the western Pacific than in the east and the dynamic change of this west-east difference remain unclear. In this paper, using the gridded surface ocean p CO 2 product constructed by the stepwise FFNN algorithm, we reported an increasing west-east CO 2 flux difference from 0.41 PgC yr -1 in 1992 to 0.73 PgC yr -1 in 2020. This increase was mainly attributed to the strengthening western Pacific carbon sink and relatively stable eastern Pacific carbon source. During El Nino events, the west-east CO 2 flux difference decreased significantly in a few years, and it then rose back rapidly when El Nino events ended. In addition, the increasing west-east difference in CO 2 uptakes during the last three decades did not lead to a higher acidification speed in the western surface temperate Pacific than the east. The greater CO 2 absorbed in the west was mainly transported to the deeper waters and caused a more significant carbon inventory change at 200-600 m than the eastern Pacific.

In vitro and in vivo efficacy of cefiderocol plus tigecycline, colistin, or meropenem against carbapenem-resistant Acinetobacter baumannii - Wentao Ni; Yifan Wang; Xinqian Ma; Yukun He; Jin Zhao; Jie Guan; Yanjun Li; Zhancheng Gao (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

Formation and evolution of secondary particulate matter during heavy haze pollution episodes in winter in a severe cold climate region of Northeast China - Ye Hong; Junying Sun; Yanjun Ma; Yangfeng Wang; Xiaolan Li; Yunhai Zhang; Ningwei Liu; Deping Zhou (Environmental Science and Pollution Research, 2022)

Physiological Responses of Ribosomal Protein S12 K43 Mutants of Corynebacterium glutamicum - Guihong Zhao; Rui Su; Meng Yuan; Hongkun Ma; Taidong Bo; Hao Jiang; Chen Wu; Yanjun Li (Current Microbiology, 2022)

Rapid changes to glaciers increased the outburst flood risk in Guangxieco Proglacial Lake in the Kangri Karpo Mountains, Southeast Qinghai-Tibetan Plateau - Yanjun Che; Shijin Wang; Yanqiang Wei; Tao Pu; Xinggang Ma (Natural Hazards, 2022)

Immunodominant membrane protein (Imp) promotes the transmission of wheat blue dwarf (WBD) phytoplasma by directly interacting with α-tubulin in leafhoppers - Lei Ding; Wenjing Lu; Yanjun Yang; Qinrong Zhong; Tong Zhou; Guiling Wang; Chengyan Song; Wendong Ma; Wei Chen; Yunfeng Wu (European Journal of Plant Pathology, 2022)

Mortality burden caused by diurnal temperature range: a nationwide time-series study in 364 Chinese locations - Min Cai; Jianxiong Hu; Chunliang Zhou; Zhulin Hou; Yanjun Xu; Maigeng Zhou; Yize Xiao; Biao Huang; Xiaojun Xu; Lifeng Lin; Tao Liu; Jianpeng Xiao; et al. (Stochastic Environmental Research and Risk Assessment, 2021)

Kinetic modeling of anaerobic degradation of plant-derived aromatic mixtures by Rhodopseudomonas palustris - Yanjun Ma; Timothy J. Donohue; Daniel R. Noguera (Biodegradation, 2021)
Rhodopseudomonas palustris is a model microorganism for studying the anaerobic metabolism of aromatic compounds. While it is well documented which aromatics can serve as sole organic carbon sources, co-metabolism of other aromatics is poorly understood. This study used kinetic modeling to analyze the simultaneous degradation of aromatic compounds present in corn stover hydrolysates and model the co-metabolism of aromatics not known to support growth of R. palustris as sole organic substrates. The simulation predicted that p -coumaroyl amide and feruloyl amide were hydrolyzed to p -coumaric acid and ferulic acid, respectively, and further transformed via p -coumaroyl-CoA and feruloyl-CoA. The modeling also suggested that metabolism of p -hydroxyphenyl aromatics was slowed by substrate inhibition, whereas the transformation of guaiacyl aromatics was inhibited by their p -hydroxyphenyl counterparts. It also predicted that substrate channeling may occur during degradation of p -coumaroyl-CoA and feruloyl-CoA, resulting in no detectable accumulation of p -hydroxybenzaldehyde and vanillin, during the transformation of these CoA ligated compounds to p- hydroxybenzoic acid and vanillic acid, respectively. While the simulation correctly represented the known transformation of p -hydroxybenzoic acid via the benzoyl-CoA pathway, it also suggested co-metabolism of vanillic acid and syringic acid, which are known not to serve as photoheterotrophic growth substrate for R. palustris .

Impact process of the aquitard to regional arsenic accumulation of the underlying aquifer in Central Yangtze River Basin - Cong Xiao; Teng Ma; Yao Du; Yanjun Liu; Rui Liu; Dongtao Zhang; Juan Chen (Environmental Geochemistry and Health, 2021)

Study on the Coincident-Loop Transient Electromagnetic Method in Seafloor Exploration—Taking Jiaodong Polymetallic Mine as a Model - Yixing Ma; Junhua Hu; Yanjun Chang; Zujian Liu (Journal of Earth Science, 2021)

Integrated risk assessment of glacier lake outburst flood (GLOF) disaster over the Qinghai–Tibetan Plateau (QTP) - Shijin Wang; Yanjun Che; Ma Xinggang (Landslides, 2020)

Macro‐scale variation and environmental predictors of flowering and fruiting phenology in the Chinese angiosperm flora - Yanjun Du; Lingfeng Mao; Simon A. Queenborough; Richard Primack; Liza S. Comita; Arndt Hampe; Keping Ma (Journal of Biogeography, 2020)
Aim The timing of reproduction is a major determinant of the geographical distribution of plant species and resulting patterns of community assembly, yet few studies have assessed how the reproductive phenology of plant assemblages varies across large geographical and environmental gradients. In addition, it remains poorly known to what extent phenological trends and their drivers differ between flowering and fruiting phases or among different growth forms. To address these knowledge gaps, we examined the reproductive phenology and potential climatic drivers in herbaceous and woody species in ecosystems across China that varied in climate (temperate to tropical) seasonality and elevation. Location China. Methods We used data from the Flora Republicae Popularis Sinicae to estimate angiosperm flowering ( n = 16,717 species) and fruiting ( n = 11,605) phenology for 100 x 100 km grid cells ( n = 943) throughout China. We assessed large‐scale geographical trends in mean flowering and fruiting date and the time needed for fruit development. The relationships of these phenological variables with seven climate variables were examined using both ordinary and spatial linear regression. Results Higher latitudes and elevations had considerably reduced length of the reproductive season, with later flowering and earlier fruiting than lower latitudes and elevations. Woody plant assemblages flowered markedly earlier and needed three times longer for fruit development, and tended to show steeper geographical trends in reproductive phenology than herbaceous assemblages. Herbs and woody species differed strongly in their climatic triggers of flowering but largely shared the same cues for fruiting. Main conclusions Woody species compensate for longer seed development times by an earlier onset of flowering, yet reproduction in both life‐forms has stronger climatic constraints. Distinct climatic drivers suggest that herbaceous and woody species assemblages will respond differently to climate change. Overall, our findings underpin the role of reproductive phenology as a key biological mechanism through which climate shapes large‐scale geographical trends in species richness, phylogenetic diversity and community assembly.

A multiple-proxy stalagmite record reveals historical deforestation in central Shandong, northern China - Liangcheng Tan; Wen Liu; Tianli Wang; Peng Cheng; Jingjie Zang; Xiqian Wang; Le Ma; Dong Li; Jianghu Lan; R. Lawrence Edwards; Hai Cheng; Hai Xu; et al. (Science China Earth Sciences, 2020)

Compaction Simulator: A Novel Device for Pressure Experiments of Subsurface Sediments - Yanjun Liu; Teng Ma; Juan Chen; Ziqi Peng (Journal of Earth Science, 2020)

Adsorption Characteristics of Tetracycline onto Biochars as Affected by Solution Chemistry Conditions and Ball Milling Treatment - Xiaohan Ma; Yanjun Xin; Qinghua Yan; Xiangrui Pan; Shuaishuai Xin; Xiaomin Huang; Qinghua Chen; Guocheng Liu (Water, Air, & Soil Pollution, 2020)

microRNA-499a promotes the progression and chemoresistance of cervical cancer cells by targeting SOX6 - Yibing Chen; Yucen Song; Yanjun Mi; Huan Jin; Jun Cao; Haolong Li; Liping Han; Ting Huang; Xiaofei Zhang; Shumin Ren; Qian Ma; Zhengzhi Zou (Apoptosis, 2020)

Spatiotemporal Variations and Regional Transport of Air Pollutants in Two Urban Agglomerations in Northeast China Plain - Xiaolan Li; Xiaoming Hu; Shuaiyi Shi; Lidu Shen; Lan Luan; Yanjun Ma (Chinese Geographical Science, 2019)

Is Chinese stalagmite δ18O solely controlled by the Indian summer monsoon? - Dong Li; Liangcheng Tan; Yanjun Cai; Xiuyang Jiang; Le Ma; Hai Cheng; R. Lawrence Edwards; Haiwei Zhang; Yongli Gao; Zhisheng An (Climate Dynamics, 2019)

Identification of movement characteristics and causal factors of the Shuping landslide based on monitored displacements - Qiong Wu; Huiming Tang; Xiaohan Ma; Yiping Wu; Xinli Hu; Liangqing Wang; Robert Criss; Yi Yuan; Yanjun Xu (Bulletin of Engineering Geology and the Environment, 2019)

An evaluation of primers for detecting denitrifiers via their functional genes - Yanjun Ma; Julie L. Zilles; Angela D. Kent (Environmental Microbiology, 2019)
Summary Microbial populations provide nitrogen cycling ecosystem services at the nexus of agriculture, environmental quality and climate change. Denitrification, in particular, impacts socio‐environmental systems in both positive and negative ways, through reduction of aquatic and atmospheric nitrogen pollution, but also reduction of soil fertility and production of greenhouse gases. However, denitrification rates are quite variable in time and space, and therefore difficult to model. Microbial ecology is working to improve the predictive ecology of denitrifiers by quantifying and describing the diversity of microbial functional groups. However, metagenomic sequencing has revealed previously undescribed diversity within these functional groups, and highlighted a need to reevaluate coverage of existing DNA primers for denitrification functional genes. We provide here a comprehensive in silico evaluation of primer sets that target diagnostic genes in the denitrification pathway. This analysis makes use of current DNA sequence data available for each functional gene. It contributes a comparative analysis of the strengths and limitations of each primer set for describing denitrifier functional groups. This analysis identifies genes for which development of new tools is needed, and aids in interpretation of existing datasets, both of which will facilitate application of molecular methods to further develop the predictive ecology of denitrifiers.

Water-soluble ion components of PM10 during the winter-spring season in a typical polluted city in Northeast China - Ye Hong; Yanjun Ma; Junying Sun; Chaoliu Li; Yunhai Zhang; Xiaolan Li; Deping Zhou; Yangfeng Wang; Ningwei Liu (Environmental Science and Pollution Research, 2019)

Clinical evaluation of a panel of multiplex quantitative real-time reverse transcription polymerase chain reaction assays for the detection of 16 respiratory viruses associated with community-acquired pneumonia - Dan Zhang; Haiyan Mao; Xiuyu Lou; Junhang Pan; Hao Yan; Hongfeng Tang; Yan Shu; Yun Zhao; Xiaoli Cheng; Hong Tao; Yanjun Zhang; Xuejun Ma (Archives of Virology, 2018)

Review: Water–rock interactions and related eco-environmental effects in typical land subsidence zones of China - Teng Ma; Yao Du; Rui Ma; Cong Xiao; Yanjun Liu (Hydrogeology Journal, 2018)

Transcriptome analysis of alternative splicing in different moso bamboo tissues - Long Li; Qianqian Shi; Dan Hou; Zhanchao Cheng; Juan Li; Yanjun Ma; Xueping Li; Shaohua Mu; Jian Gao (Acta Physiologiae Plantarum, 2018)

Comparison of Two Air Pollution Episodes over Northeast China in Winter 2016/17 Using Ground-Based Lidar - Yanjun Ma; Hujia Zhao; Yunsheng Dong; Huizheng Che; Xiaoxiao Li; Ye Hong; Xiaolan Li; Hongbin Yang; Yuche Liu; Yangfeng Wang; Ningwei Liu; Cuiyan Sun (Journal of Meteorological Research, 2018)

Characteristics of Boundary Layer Structure during a Persistent Haze Event in the Central Liaoning City Cluster, Northeast China - Xiaolan Li; Yangfeng Wang; Lidu Shen; Hongsheng Zhang; Hujia Zhao; Yunhai Zhang; Yanjun Ma (Journal of Meteorological Research, 2018)

Cloning, expression profiling and promoter functional analysis of bone morphogenetic protein 2 in the tongue sole (Cynoglossus semilaevis) - Qian Ma; Yanjun Fan; Zhimeng Zhuang; Shufang Liu (Acta Oceanologica Sinica, 2018)

Establishment and Application of a Method for Rapid Determination of Total Sugar Content Based on Colorimetric Microplate - Yonggang Wang; Yanjun Jing; Feifan Leng; Shiwei Wang; Fan Wang; Yan Zhuang; Xiaofeng Liu; Xiaoli Wang; Xueqing Ma (Sugar Tech, 2017)

HOTAIR functions as a competing endogenous RNA to regulate PTEN expression by inhibiting miR-19 in cardiac hypertrophy - Yanjun Lai; Shuai He; Liming Ma; Hong Lin; Biyun Ren; Jing Ma; Xinyu Zhu; Shifang Zhuang (Molecular and Cellular Biochemistry, 2017)

Intraspecific and phylogenetic density-dependent seedling recruitment in a subtropical evergreen forest - Yanjun Du; Simon A. Queenborough; Lei Chen; Yunquan Wang; Xiangcheng Mi; Keping Ma; Liza S. Comita (Oecologia, 2017)

Physiological and anatomical responses of Phyllostachys vivax and Arundinaria fortunei (Gramineae) under salt stress - Wei Ge; Ying Zhang; Zhongyuan Sun; Juan Li; Guohua Liu; Yanjun Ma; Jian Gao (Brazilian Journal of Botany, 2017)

Phylogenetic constraints and trait correlates of flowering phenology in the angiosperm flora of C hina - Yanjun Du; Lingfeng Mao; Simon A. Queenborough; Robert P. Freckleton; Bin Chen; Keping Ma (Global Ecology and Biogeography, 2015)
Aim The phylogenetic constraint hypothesis of flowering phenology states that closely related species flower at similar times of the year. We test this hypothesis for the C hinese angiosperm flora and assess additional effects of growth form, deciduousness, pollination mode and fruit type. We further examine whether the phylogenetic conservatism of flowering phenology tends to increase from tropical to temperate latitudes. Location C hina. Methods The midpoint of flowering time for 19,631 angiosperm species present in C hina was compiled. The phylogenetic signal for flowering time was evaluated for the whole country using the B lomberg K ‐value (adjusted for circular data). We then regressed the phylogenetic signal for 28 provinces as a function of their latitude. An analysis of variance for circular data was conducted to test the differences among growth forms. W atson– W illiams tests for circular flowering data were used to compare flowering dates between deciduous and evergreen species, animal‐pollinated and wind‐pollinated species, and fleshy and non‐fleshy fruits. Results The results support the phylogenetic constraint hypothesis. The phylogenetic signal at the whole country scale was lower than that at the province scale. Phylogenetic signal was also lower at tropical latitudes than at temperate latitudes. Flowering dates were associated with biological traits, with growth form having the largest effect. Main conclusions Flowering phenology was constrained by phylogeny, and so one should account for phylogeny when studying the underlying drivers of phenology. The strength of phylogenetic conservatism appears weaker at larger scales and becomes stronger towards temperate regions. Flowering phenology also varies predictably according to biological traits such as growth form, suggesting that both phylogeny and traits could be used to inform the flowering times of species for which no phenology data are available. It remains to be tested whether the phylogenetic signal for other functional traits putatively related with flowering time also increases with latitude.

Phosphoinositide 3-Kinase Pathway Mediates Early Aldosterone Action on Morphology and Epithelial Sodium Channel in Mammalian Renal Epithelia - Yuan Zhou; Xuewei Chen; Xiao Liu; Hujie Lu; Ying Li; Hui Zhu; Gaihong An; Na Zhang; Jianning Zhang; Qiang Ma; Yanjun Zhang (The Journal of Membrane Biology, 2014)

The rice OsDG2 encoding a glycine-rich protein is involved in the regulation of chloroplast development during early seedling stage - Quan Jiang; XiaoJing Ma; XiaoDi Gong; JianHui Zhang; Sheng Teng; JianLong Xu; DongZhi Lin; YanJun Dong (Plant Cell Reports, 2014)

Application of exogenous substances reduces tobacco-specific nitrosamines content by regulating biosynthesis of nicotine and nitrite in burley tobacco - Siwei Liang; Jinpeng Yang; Jun Zhou; Jun Yu; Yanjun Ma; Ruoshi Bai; Fangsen Xu; Chunlei Yang (Acta Physiologiae Plantarum, 2013)

Characterization of Two Mammalian Cortical Collecting Duct Cell Lines with Hopping Probe Ion Conductance Microscopy - Xuewei Chen; Hui Zhu; Xiao Liu; Hujie Lu; Ying Li; Jing Wang; Hongtao Liu; Jianning Zhang; Qiang Ma; Yanjun Zhang (The Journal of Membrane Biology, 2013)

A comparison study of the simulation accuracy between WRF and MM5 in simulating local atmospheric circulations over Greater Beijing - ZhenXin Liu; ShuHua Liu; Fei Hu; Ju Li; YanJun Ma; HePing Liu (Science China Earth Sciences, 2012)

Effect of NaCl on leaf H+-ATPase and the relevance to salt tolerance in two contrasting poplar species - Xiuying Ma; Lin Deng; Jinke Li; Xiaoyang Zhou; Niya Li; Decai Zhang; Yanjun Lu; Ruigang Wang; Jian Sun; Cunfu Lu; Xiaojiang Zheng; Eberhard Fritz; et al. (Trees, 2010)

Application of enzyme-linked immunosorbent assay for quantification of the insecticides imidacloprid and thiamethoxam in honey samples - Huixin Ma; Yanjun Xu; Qing X. Li; Ting Xu; Xintong Wang; Ji Li (Food Additives & Contaminants: Part A, 2009)

Cyclophosphamide promotes pulmonary metastasis on mouse lung adenocarcinoma - Shuli Man; Yanjun Zhang; Wenyuan Gao; Lulu Yan; Chaoyi Ma (Clinical & Experimental Metastasis, 2008)

Uncertainties in stock assessment and the precautionary management suggestions for the anchovy (Engraulis japonicus) stock in the Yellow Sea - Yanjun Wang; Qun Liu; Yuxia Ma (Journal of Ocean University of China, 2007)

Improved use of organic phosphate by Skeletonema costatum through regulation of Zn2 + concentrations - Yanjun Shi; Hanhua Hu; Runyu Ma; Wei Cong; Zhaoling Cai (Biotechnology Letters, 2004)